In vitro antidiabetic of Cemumar (Micromelum pubescens), Tebengau (Ehretia laevis) and Kedondong (Spondias dulcis) leaves extract - Nurirdayu, Jantan (Universiti Malaysia Perlis, 2011)
Access is limited to UniMAP community.